Discapacidad, invalidez, incapacidad para el trabajo y trabalenguas: ¿si tengo discapacidad y trabajo, puedo cobrar pensión de invalidez? - Bregaglio Lazarte, Renata (2016)
The article focuses on a new problem that requires an adequate legal answer that respects the rights of the persons with disabilities: are all persons with disabilities incapacitated for work? This question tries to make a critical assessment of the traditional systems of social security that assumed that any disability led to the end of the productive life. However, that differs completely from the view of the social model of disability that states that disability comes from the social barriers and not from the persons. If disability is not the same as incapacity to work, how and when should this latter figure be applied? The existence of both figures requires us to differentiate them. The hypothesis is that these figures are different but may coexist at the same time.